Production of gelatin replacers from Malaysian tuberous plants - Jaswir, Irwandi; Kamalurudin, Nur Ain Zafirah; Mohd. Salleh, Hamzah (IIUM Press, 2011)
This research ","'ork was conducted to explore lIll: potential of tuberous plall1s as sources ofgelatin replacers. The tuber of yam and sweet potato commonly consumed and grown in Malaysia were used as raw material. The starch compounds were extracted by using different process condition rhat will optimize the extraction of starch. The design of experiment and statistical analysis were done using statistical software Design Expert for optimization. The process conditions seleeted were the alkali concell1ration. sleep temperarure and steep time. The effect of Ihc three process paramelers were evaluaTed for their effeCT on yield, protein content and ~iscosily of sla«:h. Two level full factorial design was used TO invesTigaTe The process. All main effecTS and interactions were found TO have significanT effect on prolein content in the e.xtractcd STarch, The viscosity of The starch was affeCTed by the three mam effecls and the three two-factor interaction effects. Conditions thai produced a high starch yield. low prOTein and high viscosily were 0.1% alkali concentration. 25°C temperature and 30min steep Time for bolh yam and sweet potaTO starch.